Effect of Facial Fillers on Post-rhinoplasty edema: A Hypothesis Based on Literature Review - Maamari, Salwa Al; Vansteelant, Géraldine; Appan, Shirrushtii; D'Souza, Alwyn (Facial Plastic Surgery, 2024)
The quest to achieve younger and media-driven facial aesthetics has resulted in an exponential increase in the use of facial fillers. Inevitably, this has meant that it is now commonplace for facial plastic surgeons to have patients with fillers in the face. In the senior author's experience (A.R.D.), it was observed that patients with facial fillers experienced persistent edema post-rhinoplasty. It was, therefore, hypothesized that this prolonged edema may be related to fillers affecting the lymphatic drainage impacting postoperative edema following facial surgery.This article aims to gather evidence from wider literature to support the hypothesis that fillers do indeed compromise lymphatic drainage. A narrative literature review was performed using selective articles on fillers and post-rhinoplasty edema. A methodological analysis was then followed to develop a standard theory characterized through the discussion.It is theorized that due to their hydrophilic characteristics, hardness, volume, and backflow phenomena, hyaluronic acid fillers can lead to prolonged edema. In addition, they can either directly block or indirectly exert pressure on the lymphatic pathways and hinder drainage.The research findings support the hypothesis that facial fillers impact postoperative facial edema. Further research is required to objectively measure the effect of fillers on facial lymphatic drainage.The level of evidence is IV.
Keywords: hyaluronic acid fillers; rhinoplasty; prolonged post-rhinoplasty edema; facial fillers; persistent edema; facial edema; lymphatic channels